Parasitoid lalat pengorok daun pada pertanaman kentang dan tumbuhan Liar di wilayah pangalengan - Purnomo Purnomo; Aunu Rauf; Soemartono Sosromarsono; Teguh Santoso (Perhimpunan Entomologi Indonesia, 2005)
Parasitoids of Leafminer Fly on Potato Fields and Non-Crop Vegetation in Pangalengan Area. The damage leaves of potato and non-crop vegetation caused by leafminer fly Liriomyza huidobrensis (Blanchard) (Diptera: Agromzidae) were collected during August-October 2000 in Pangalengan area to evaluate the role of non-crop vegetation on the abundance of leafminer fly and its parasitoids. The leaves were placed into the bowls. The fly and parasitoid that emerged from the leaves were noted afterwards. The result of this survey showed that six families of plant were the host of L. huidobrensis on non-crop vegetation around the potato plantation. Those families are, Amaranthaceae, Asteraceae, Chenopodiaceae, Convolvulaceae, Malvaceae, and Solanaceae. The most abundant of non-crop vegetation found in the field was galinggang (Galinsoga Parviflora). The parasitoids that emerge from non-crop vegetation were Hemiptarsenus varicornis (Girault) (Hymenoptera: Eulophidae) and Opius sp. (Hymenoptera: Braconidae). The proportion of emerged fly were 68.5% from non-crop vegetation and 58.8% from potato, while those of parasitoids were 31.5% from non-crop vegetation and 41.2% from potato. Generally, non-crop vegetation in Pangalengan more potent as reservoar of pest than parasitoids.